Generation of GM-CSF-producing antigen-presenting cells that induce a cytotoxic T cell-mediated antitumor response. (1st January 2020) - Mashima, Hiroaki; Zhang, Rong; Kobayashi, Tsuyoshi; Hagiya, Yuichiro; Tsukamoto, Hirotake; Liu, Tianyi; Iwama, Tatsuaki; Yamamoto, Masateru; Lin, Chiahsuan; Nakatsuka, Ryusuke; Mishima, Yuta; Watanabe, Noriko; et al.
ABSTRACT: Immunotherapy using dendritic cells (DCs) is a promising treatment modality for cancer. However, the limited number of functional DCs from peripheral blood has been linked to the unsatisfactory clinical efficacies of current DC-based cancer immunotherapies. We previously generated proliferating antigen-presenting cells (APCs) by genetically engineering myeloid cells derived from induced pluripotent stem cells (iPSC-pMCs), which offer infinite functional APCs for broad applications in cancer therapy. Herein, we aimed to further enhance the antitumor effect of these cells by genetic modification. GM-CSF gene transfer did not affect the morphology, or surface phenotype of the original iPSC-pMCs, however, it did impart good viability to iPSC-pMCs. The resultant cells induced GM-CSF-dependent CD8 + T cell homeostatic proliferation, thereby enhancing antigen-specific T cell priming in vitro . Administration of the tumor antigen-loaded GM-CSF-producing iPSC-pMCs (GM-pMCs) efficiently stimulated antigen-specific T cells and promoted effector cell infiltration of the tumor tissues, leading to an augmented antitumor effect. To address the potential tumorigenicity of iPSC-derived products, irradiation was applied and found to restrict the proliferation of GM-pMCs, while retaining their T cell-stimulatory capacity. Furthermore, the irradiated cells exerted an antitumor effect equivalent to that of bone marrow-derived DCs obtained from immunocompetent mice. Additionally, combination with immune checkpoint inhibitors increased the infiltration of CD8 + or NK1.1 + effector cells and decreased CD11b + /Gr-1 + cells without causing adverse effects. Hence, although GM-pMCs have certain characteristics that differ from endogenous DCs, our findings suggest the applicability of these cells for broad clinical use and will provide an unlimited source of APCs with uniform quality.